Lafoeina tenuis - Moura, Carlos J. (Zenodo, 2015)
Lafoeina tenuis (fig. 3A) Lafoeina tenuis G. O. Sars, 1874: 95, 119–121, pl. 5 figs. 1–5.— Cornelius, 1995a: 197 –199, fig. 45.— Vervoort, 2006: 225 –226, figs. 7 no. 4; 8 no. 1; 10d–i.— Bouillon et al ., 2004: 131, figs. 69E–G. Material studied . Ormonde, stn 1 : few polyps, on cauli of Zonaria tournefortii , DBUA 1522.07. Ormonde, stn 2 : few polyps, on Zonaria tournefortii , DBUA 1522.01. Ormonde, stn 3 : very frequent, on cauli of Zonaria tournefortii and calcified Bryozoa, DBUA 1522.02. Ormonde, stn 4 : frequent, covering all over some Zonaria tournefortii , DBUA 1522.03. Gettysburg, stn 5 : few polyps, on Zonaria tournefortii , DBUA 1522.04. Gettysburg, stn 6 : few polyps, on two species of algae. Gettysburg, stn 7 : frequent on algae, DBUA 1522.06. Gettysburg, stn 8 : few polyps, on Zonaria tournefortii . Gettysburg, stn 9 : very frequent on Zonaria tournefortii , also overgrowing Sertularella ellisii , DBUA 1522.08. Gettysburg, stn 10 : very abundant; on algae and colonies of Sertularella gayi and S. ellisii , DBUA 1522.09. Reported distribution . Northeast Atlantic.—Widely distributed in the Northeast Atlantic: Azores (Cornelius 1992, 1995a; Vervoort 2006), Madeira (Cornelius 1995a), Gorringe (present study), mainland Portugal (personal observation), Spain (García-Corrales et al. 1979; Ramil 1988; Altuna & García-Carrascosa 1990; Alvarez-Claudio 1993; Altuna 1994a, b; Álvarez-Claudio & Anadón 1995; Medel & López-González 1996; Ramil et al. 1998a); Bay of Biscay (Gourret 1906); British Isles (e.g. Hincks 1868; Cornelius 1995a; Howson & Picton 1997; France (Cornelius 1995a); Iceland (Hincks 1874); Norway (Sars 1869, 1874; Hincks 1874; Christiansen 1972); Sweden (Jagerskiold 1971; Calder 2012); Baltic Sea/North Sea (Broch 1928). Mediterranean.—Widely spread across the western Mediterranean: Spain (Gili 1986; García Carrascosa 1981; Roca 1986); France (Picard 1951b; Bellan-Santini 1970; Galea 2007), and Italy (e.g. Rossi 1961; Montanari & Morri 1977; Morri 1979, 1980, 1981). Recently ...